2007
DOI: 10.1063/1.2799988
|View full text |Cite
|
Sign up to set email alerts
|

A density functional theory study on the binding of NO onto FePc films

Abstract: To develop an atomistic understanding of the binding of NO with iron phthalocyanine (FePc), the interaction between NO (an electron withdrawing gas) and NH3 (an electron donating gas) with an isolated FePc molecule (monomer) was compared with density functional theory. The simulations show that NO strongly chemisorbs to the Fe metal and physisorbs to all the nonmetal sites. Additionally, when NO physisorbs to the inner ring nitrogens, NO subsequently undergoes a barrierless migration to the deep chemisorption … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 44 publications
(31 reference statements)
2
21
0
Order By: Relevance
“…However, there exists one theoretical study of diffusion of NO on FePc, which predicts diffusion barriers on the order of ∼50%-100% of the desorption barrier. 74 Applied to our case and noting that at adsorption T = 70 K, which corresponds to k B T = 6 MeV, much smaller than the estimated desorption energies, this suggests a limitation of diffusion of NH 3 on FePc. A similar argument might apply for diffusion from any second-layer NH 3 on the Au(111) surface to the FePc.…”
Section: Ammonia Adsorption On Fepc Monolayers: Ammonia Speciesmentioning
confidence: 99%
“…However, there exists one theoretical study of diffusion of NO on FePc, which predicts diffusion barriers on the order of ∼50%-100% of the desorption barrier. 74 Applied to our case and noting that at adsorption T = 70 K, which corresponds to k B T = 6 MeV, much smaller than the estimated desorption energies, this suggests a limitation of diffusion of NH 3 on FePc. A similar argument might apply for diffusion from any second-layer NH 3 on the Au(111) surface to the FePc.…”
Section: Ammonia Adsorption On Fepc Monolayers: Ammonia Speciesmentioning
confidence: 99%
“…A DFT study of NO attachment to the free FePc molecule arrived at a similar value for the Fe-NO distance(1.71 Å) and predicted that the Fe center loses 0.28 e À as a result of NO coordination, while the NO ligands gains 0.31 e À (the difference is compensated by the phthalocyanine ligand). Related calculations were performed for a trimer of parallel FePc complexes (as a model for a multilayer film) and for a monolayer film (without substrate)[768]. From the…”
mentioning
confidence: 99%
“…Only binding to the Zn metal center of the ZnPc monomer was investigated since numerous experimental and theoretical studies have shown that preferential binding occurs to the metal center. 23,48,49 Additionally, experimental sensor data show the response differs for a given analyte on different MPc films consistent with bonding to the metal centers. 50 Various initial geometries of analyte binding to the Zn metal center were sampled to determine the lowest energy binding conformation for each analyte.…”
Section: Methodsmentioning
confidence: 91%
“…The small charge transfer for these weakly bound analytes agrees with that observed in a previous study using the Bader charge analysis method that showed electron donating physisorbates donated 0.07e − to the FePc metal center. 23,68,69 Additionally, the analysis of the plot shows a modest linear dependence between the magnitude of electron donation from the analyte to the ZnPc monomer and their ZnPc binding energies ͑R 2 = 0.67͒. Although the DFT calculations show that charge transfer occurs on analyte binding to the Zn metal of the ZnPc monomer, this charge transfer is small and only a linear function of the binding energy.…”
Section: A Znpc Binding Versus Lewis Basicitymentioning
confidence: 97%
See 1 more Smart Citation